A New Software Tool to Facilitate NURB Based Geometries in Acoustic Design. Issue 1 (March 2014) - O'Keefe, John; Ashtiani, Payam; Grant, David
Non-rational uniform B-splines (NURBs) are liberating acoustic design. Geometrical acoustics is no longer limited to flat surfaces. For decades, curved surfaces in computer models had to be broken down into a series of contiguous flat surfaces; a procedure prone to inaccuracy. With NURBs this is no longer the case. A new software tool has been developed by the authors, called NRAT, intended to facilitate acoustic design in NURB based geometries. Two parameters have been developed to quantify the efficiency of reflectors as they are being designed. They are called Reflector Efficiency (RFE) and Receiver Coverage (RCC). The two are quoted together, much like a blood pressure reading might be. The two parameters are required for reasons that became apparent to the authors as the NRAT tool was being developed. A small reflector, perhaps one that might be part of an array, may have a very high percentage of its surface area effectively casting reflections to the audience (perhaps 85%) but those reflections may only cover a small proportion of the audience area (say, 12%). Conversely, a large reflector, for example the side wall of a shoe box shaped concert hall, may only have a small area casting reflections to the audience – in our experience, in the range of 6%. But this small zone efficiently casts reflections across the expanse of the audience, sometimes as much as 90% or more. The quantification of the two RFE/RCC scenarios presented above would be, respectively, "85 over 12" and "6 over 90". Two case studies are presented.